Notes sur les méthodes de dépistage pour la coccidiose aviaire - Belot, J.; Pangui, JL. (Tropicultura, 1987)
Avian coccidiosis : rnethods for recovering oocysts from litter. A network of training Centres for Young Farmers (C.F.J.A.) is being installed in Cameroon. The type of activities at the C.F.J.A. deserves interest, as the training is based on verbal and practical one with discussions and exchanges of views playing a large role. Only young couples households owing agricultural land in their own village are recruited. Women receive a special training (hygiene, feeding, child welfare, sewing, embrodery). At the outcome of this course which lasts 8 till 10 months (farming season) the families return to their village with a pair of draught animals, agricultural equipment and the food crops they have produced at the C.F.J.A.